2022
DOI: 10.1371/journal.pone.0262370
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary paths to macrolide resistance in a Neisseria commensal converge on ribosomal genes through short sequence duplications

Abstract: Neisseria commensals are an indisputable source of resistance for their pathogenic relatives. However, the evolutionary paths commensal species take to reduced susceptibility in this genus have been relatively underexplored. Here, we leverage in vitro selection as a powerful screen to identify the genetic adaptations that produce azithromycin resistance (≥ 2 μg/mL) in the Neisseria commensal, N. elongata. Across multiple lineages (n = 7/16), we find mutations that reduce susceptibility to azithromycin converge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…We used a protocol based on the work of Raisman et al 2022. In their study, they were able to induce resistance to azithromycin in N. elongata by performing crossover E-tests [ 40 ]. In contrast, Levin-Reisman et al 2017 induced AMR via continuing the cyclical intermittent antibiotic exposure set-up for up to 17 cycles [ 8 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used a protocol based on the work of Raisman et al 2022. In their study, they were able to induce resistance to azithromycin in N. elongata by performing crossover E-tests [ 40 ]. In contrast, Levin-Reisman et al 2017 induced AMR via continuing the cyclical intermittent antibiotic exposure set-up for up to 17 cycles [ 8 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their study, they were able to induce resistance to azithromycin in N. elongata by performing crossover E-tests [ 40 ]. In contrast, Levin-Reisman et al 2017 induced AMR via continuing the cyclical intermittent antibiotic exposure set-up for up to 17 cycles [ 8 , 40 ]. An additional important consideration is that gonococcal resistance to CRO is more difficult to induce in vitro compared to AZM and ampicillin [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in vitro evolution experiments can reveal the spontaneous mutations caused by DNA replication and repair errors which increase mean fitness in new selective environments ( 148 ), and are quick and easy to implement in the research laboratory due to the short generation times of Neisseria (~60 min). Using this approach, multiple tandem duplications in the locus encoding the 50S ribosomal L34 protein ( rpmH ) and the intergenic region proximal to the 30S ribosomal S3 protein ( rpsC ) were identified to increase resistance (≥2 μg/mL) to the macrolide antibiotic azithromycin in the commensal N. elongata in 20 days (or approximately 480 generations) ( 149 ). A similar experiment also described an identical 7LKRTYQ12 sequence duplication in rpmH as a transient steppingstone to high level azithromycin resistance in N. gonorrhoeae ( 150 ).…”
Section: Canary In the Coal Mine: The Benefits Of Surveillance In Com...mentioning
confidence: 99%
“…Recent studies have suggested that azithromycin may promote antimicrobial resistance to other classes of antimicrobials via inducing mutations that act as stepping-stones to antimicrobial resistance. [4][5][6] In vitro, culture experiments with Mycobacterium smegmatis have found that antimicrobial-induced mutations in ribosomal proteins reduce susceptibility to various antimicrobials in a stepping-stone manner. 4 Ciprofloxacin, for example, first selects for mutations in four ribosomal proteins.…”
Section: Introductionmentioning
confidence: 99%